Effect of Teachers Training Workshop Outcomes on Real Classroom Situations of Undergraduate Medical Students - Baral, N.; Nepal, A.K.; Paudel, B.H.; Lamsal, M. (Kathmandu University Medical Journal, 2017)
Background Faculty development by conducting regular training, workshops and research related to medical education has been a key feature to upgrade quality of medical education. Objective The aim of this study was to explore responses of the health science teachers, students and peers after the workshop after providing training on student assessment tools and teaching-learning methods. Method Two teacher-training workshops were conducted to the faculty members of B.P. Koirala Institute of Health Sciences from the departments of basic, clinical and allied sciences in Oct. 2010 and Jan. 2011. Qualitative questionnaire based study was conducted, and the questions were validated before the study by expert peer review process. The effect of the training workshop in real classroom outcomes was assessed incorporating student’s feedback, evaluation by peers and the self-evaluation by the teacher trainees. Result Pre-test and post-test scores of the participating teachers, before and after the workshop were 62.53 and 71.17 respectively. Among the participants 90.3% teachers expressed enhanced in their role as a teacher for medical undergraduates after the workshop. Conclusion In present study, the faculty members showed accrued interest to participate in teacher’s training workshops. The peer evaluation of teacher’s performance in their real classroom situations were rated higher than evaluation by the students. Therefore, such training workshops will have a greater impact on the ability of teachers in effective teaching in real classroom situations.